Per1 gene polymorphisms influence the relationship between brain white matter microstructure and depression risk - Zhao, Rui; Sun, Jin-Bo; Deng, Hui; Cheng, Chen; Li, Xue; Wang, Fu-Min; He, Zhao-Yang; Chang, Meng-Ying; Lu, Li-Ming; Tang, Chun-Zhi; Xu, Neng-Gui; Yang, Xue-Juan; et al. (Frontiers in Psychiatry, 2022)
Background: Circadian rhythm was involved in the pathogenesis of depression. The detection of circadian genes and white matter (WM) integrity achieved increasing focus for early prediction and diagnosis of major depressive disorder (MDD). This study aimed to explore the effects of PER1 gene polymorphisms (rs7221412), one of the key circadian genes, on the association between depressive level and WM microstructural integrity. Methods: Diffusion tensor imaging scanning and depression assessment (Beck Depression Inventory, BDI) were performed in 77 healthy college students. Participants also underwent PER1 polymorphism detection and were divided into the AG group and AA group. The effects of PER1 genotypes on the association between the WM characteristics and BDI were analyzed using tract-based spatial statistics method. Results: Compared with homozygous form of PER1 gene (AA), more individuals with risk allele G of PER1 gene (AG) were in depression state with BDI cutoff of 14 (χ2 = 7.37, uncorrected p = 0.007). At the level of brain imaging, the WM integrity in corpus callosum, internal capsule, corona radiata and fornix was poorer in AG group compared with AA group. Furthermore, significant interaction effects of genotype*BDI on WM characteristics were observed in several emotion-related WM tracts. To be specific, the significant relationships between BDI and WM characteristics in corpus callosum, internal capsule, corona radiata, fornix, external capsule and sagittal stratum were only found in AG group, but not in AA group. Conclusion: Our findings suggested that the PER1 genotypes and emotion-related WM microstructure may provide more effective measures of depression risk at an early phase.